2020
DOI: 10.3389/fmicb.2020.00568
|View full text |Cite
|
Sign up to set email alerts
|

Site-Specific Conditions Change the Response of Bacterial Producers of Soil Structure-Stabilizing Agents Such as Exopolysaccharides and Lipopolysaccharides to Tillage Intensity

Abstract: Bacterial Response to Tillage Intensity to tillage intensity had higher potential for exopolysaccharide and lipopolysaccharide production specifically under reduced tillage. This could be especially crucial for aggregate stability, as polysaccharides produced by different taxa have different "gluing" efficiency. Overall, our data indicate that tillage intensity could affect aggregate stability by both influencing the absolute abundance of genes involved in the production of exopolysaccharides and lipopolysacch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 76 publications
0
8
0
Order By: Relevance
“…In these studies, genes related to the production of exopolysaccharides and lipopolysaccharides ( wza, algE, algJ, wcaB, wcaF, wcaK, amsJ, kpsE, epsG, epsA, sacB, wzt, lptF, lptG, lptC ) were observed to increase in biocrusts compared to bulk soil samples (Cania, Vestergaard, Kublik, et al, 2020). Similar techniques were also used to demonstrate that the improved aggregate stability associated with reduced tillage practices at some sites was associated with an increase in the abundance of genes associated with exopolysaccharide and lipopolysaccharide production (Cania, Vestergaard, Suhadolc, et al, 2020), although at others no differences were observed (Cania et al, 2019; Cania, Vestergaard, Suhadolc, et al, 2020). It was noted by the authors of this study that due to the lack of gene sequence data regarding the production of EPS by other organisms, these studies are biased towards bacteria (Cania, Vestergaard, Suhadolc, et al, 2020).…”
Section: Molecular Genetic Techniques and Their Ability To Provide In...mentioning
confidence: 99%
See 2 more Smart Citations
“…In these studies, genes related to the production of exopolysaccharides and lipopolysaccharides ( wza, algE, algJ, wcaB, wcaF, wcaK, amsJ, kpsE, epsG, epsA, sacB, wzt, lptF, lptG, lptC ) were observed to increase in biocrusts compared to bulk soil samples (Cania, Vestergaard, Kublik, et al, 2020). Similar techniques were also used to demonstrate that the improved aggregate stability associated with reduced tillage practices at some sites was associated with an increase in the abundance of genes associated with exopolysaccharide and lipopolysaccharide production (Cania, Vestergaard, Suhadolc, et al, 2020), although at others no differences were observed (Cania et al, 2019; Cania, Vestergaard, Suhadolc, et al, 2020). It was noted by the authors of this study that due to the lack of gene sequence data regarding the production of EPS by other organisms, these studies are biased towards bacteria (Cania, Vestergaard, Suhadolc, et al, 2020).…”
Section: Molecular Genetic Techniques and Their Ability To Provide In...mentioning
confidence: 99%
“…Similar techniques were also used to demonstrate that the improved aggregate stability associated with reduced tillage practices at some sites was associated with an increase in the abundance of genes associated with exopolysaccharide and lipopolysaccharide production (Cania, Vestergaard, Suhadolc, et al, 2020), although at others no differences were observed (Cania et al, 2019; Cania, Vestergaard, Suhadolc, et al, 2020). It was noted by the authors of this study that due to the lack of gene sequence data regarding the production of EPS by other organisms, these studies are biased towards bacteria (Cania, Vestergaard, Suhadolc, et al, 2020). It was also noted that the actual production of exo‐ and lipo‐polysaccharides could differ depending on environmental factors (carbon availability, temperature, soil pH, etc) and the application of more metatranscriptomics analysis of the soil environment would be desirable to examine these factors given that even though genes may be present, they may not always be actively expressed (see further discussion below) (Cania et al, 2019).…”
Section: Molecular Genetic Techniques and Their Ability To Provide In...mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, taxonomical data generated through metagenomic approaches should be considered cautiously depending on the taxonomical level and specific biological and/or ecological functions. While both conventional and conservation tillage increase the abundance of Actinobacteria (Hartman et al, 2018;Babin et al, 2019), Cania et al (2020) demonstrated that low tilling intensity favors those harboring a higher potential to produce exo-and lipopolysaccharides. These biomolecules are crucial in soil macroaggregate formation and stability and, therefore, play crucial roles in preventing severe erosion events and ecological niche homogenization.…”
Section: Impact Of Tillage Practices On Soil Microbiotamentioning
confidence: 99%
“…Only in areas with sufficient water storage in the soil can yield losses that remain within acceptable limits [24]. However, the geographical distribution of soils and their quality and health varies spatially on all scales, from climatic zones to individual fields [25]. Therefore, not only the protection of soil and the preservation of its functions, but also the use of soils under the aspect of resilience to crises such as the COVID-19 pandemic must be approached site-specifically.…”
Section: Soil Healthmentioning
confidence: 99%